Patient monitoring and education over a tailored digital application platform for congenital heart disease: A feasibility pilot study. (1st September 2022) - Nashat, Heba; Habibi, Hajar; Heng, Ee Ling; Nicholson, Conor; Gledhill, Jonathan R.; Obika, Bernard D.; Yassaee, Arrash A.; Markides, Vias; McCleery, Piers; Gatzoulis, Michael A.
Abstract: Background: Patients with adult congenital heart disease (ACHD) are a rapidly growing cardiovascular population with increasing health needs and co-morbidities. Furthermore, their management requires frequent and ongoing hospital visits which can be burdensome. Digital health and remote monitoring have been shown to have a vast potential to enhance delivery of healthcare for patients, reducing their need for travel to clinic appointments therefore reducing costs to the patient and the healthcare service. Methods: Patients over the age of 16 with a diagnosis of ACHD were invited to use the tailored digital application too. They were monitored for a period of 6 months. Information on patient demographics, time using the application, flagged events that prompted clinical reviews and their feedback through patient surveys were collected. Results: A total of 103 patients were enrolled and registered to use the digital application tool. There were 57 (56%) males, median age at the time of enrolment was 39 (16–73) years. The majority (96%) had a moderate or complex ACHD according to the ACC/AHA classification. There was a total of 7 modules that were completed on a weekly basis. The median length of a participant session was 2.2 min and the mean time to complete a module was 21 s. In total, 35 (67%) felt that the application helped them better manage their cardiac condition. Almost all (94%) of patients expressed that they would like to continue using the application beyond the pilot. There were 18 flagged events during the 6 month observation period, and 50% of received early clinical intervention. Conclusion: Application based remote monitoring in this select group was well received and potentially holds large benefit to patients both clinically and economically. There were no safety concerns in our pilot feasibility study. Our data may inform much needed and timely investment in digital health. Highlights: Digital technology and remote monitoring are an increasing resource for patients and healthcare professionals. The use of remote monitoring applications is cost effective for both patients and health care services. Remote monitoring may be incorporated into standard medical care for patients.